Influence of Initial Grain Size on the Formation of Sigma and its Effect on Corrosion and Wear Properties of 2205 Duplex Stainless Steel - Kısasöz, Burçin Özbay (Elsevier, 2025)
In this work, grain size dependent sigma phase formation was studied in AISI 2205 alloy. For this purpose, samples with two different grain sizes were held at 800 ◦C for 15 min and 60 min followed by quenching. Moreover, the microstructure, corrosion, and wear properties of the samples were determined. The sigma phase morphology was directly affected by the initial grain size, and continuous and fine grain precipitates were observed in coarser grain structure of the AISI 2205 duplex stainless steel. On the other hand, the finer grain structure of the alloy enhanced the growth mechanism of the sigma, and the sigma phase ratio was increased at a longer process time. The highest corrosion rate and severe corrosion damage were obtained in coarser grain structure of the alloy following the process at 800 ◦C for 60 min. Contrary, continuous and fine grain sigma precipitates improved the wear properties in this sample and the wear rate values were decreased to 2.56⋅10ˉ⁴ 4 mm³/Nm and 0.77⋅10ˉ⁴ 4 mm³/Nm after 15 min and 60 min of heat treatment process.
Keywords: Duplex Stainless Steel; Sigma Precipitation; Corrosion; Wear